Undernutrition and associated factors among school-age children in Wolaita Zone, South Ethiopia: a comparative cross-sectional study - Meskele, Dereje Kutafo; Abiso, Temesgen Lera; Belete, Tinsae Bekele; Koyira, Mengistu Meskele; Dake, Samson Kastro (Frontiers in Nutrition, 2024)
Background: Nutritional deficiencies in school-age children are a public health concern, especially in resource-limited countries. A school feeding program is the provision of food on-site or taken home to reduce hunger. It is implemented in several developing nations; however, little is known about the association of school feeding programs with the nutritional status of school-age children in the study areas.Objectives: To determine the magnitudes and associated factors of undernutrition among school-age children with school-feeding programs (SFP) and non-school feeding programs (N-SFP) in Kindo Didaye woreda, South Ethiopia.The school-based comparative cross-sectional study was conducted at Kindo Didaye district from May to June 2023. A total of 612 participants were included in the study. Data were collected from each selected student's parents by using a structured interviewer-administered questionnaire. Weight and height of the children were measured and a household dietary diversity assessment was conducted. Data were analyzed by using SPSS version 25. A binary logistic regression analysis was carried out. A p-value of less than 0.05 and 95% CI were used to declare a statistically significant association.The magnitude of undernutrition among school-age children was 38.9%; 43.3% in schools with SFP and 34.5% in schools with N-SFP. Stunting was 24.1% among children in schools with SFP and 16% in N-SFP, whereas thinness was 33.8% among children in SFP and 25.6% in N-SFP.Children who are in the older age group (AOR=4.4, 95%CI; 2.22-8.85), consume less than three meals per day at home (AOR=6.03; 95%CI 3.9-9.3), and do not eat breakfast at all before going to school (AOR=3.5; 95%CI 1.15-10.76) were more likely to become undernourished. Children whose fathers attended secondary and above education (AOR=0.52; 95% CI (0.27-0.971) had lower odds of becoming underweight.The magnitude of undernutrition was high in the current study. Existing interventions that work to improve the nutritional status of school-age children should be strengthened. Children should consume any type of food as breakfast at home before going to school regardless of the presence of school feeding programs, and at least three times a day.